PENGARUH PASTA EKSTRAK TOMAT (Lycopersicon esculentum Mill.) TERHADAP PENGHILANGAN STAIN EKSTRINSIK PADA PERMUKAAN GIGI, GIGI TIRUAN, DAN PLAT RESIN AKRILIK - , INTEN PRATIWI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Chromogen from food and beverages can cause extrinsic stain on the surface of teeth, acrylic resin denture teeth, and denture base. The use of hydrogen peroxide has evolved as additional ingredient of toothpaste and denture cleanser to remove extrinsic stain. Tomatoes (Lycopersicon esculentum Mill.) contain hydrogen peroxide. The aim of this study was to determine the effect of extract of tomato paste (Lycopersicon esculentum Mill.) to remove extrinsic stain on the surface of teeth, acrylic resin denture teeth, and denture base. The subjects of this study were 15 first maxillary premolar extracted teeth, 15 first maxillary premolar acrylic resin denture teeth, and 15 acrylic resin denture base. Forty five subjects were immersed in a solution of black tea, and then brushed with basic paste as negative control, extract of tomato paste, and stain removal toothpaste (ZACTï) as positive control. The surface image was taken using DSLR camera before and after staining, after brushing treatment with paste. Intensity of gray level image was measured using ImageJ software. Difference in intensity of gray level image before staining and after brushing was obtained and analyzed statistically. The result of one way Anova test in each material showed significant difference between mean of groups of the type of paste to the removal of extrinsic stain (p<0,05). LSD test showed significant differences between mean of groups of basic paste and extract of tomato paste, basic paste and ZACTï toothpaste (p<0,05). There was no significant difference between mean of group of extract of tomato paste and ZACTï toothpaste (p>0,05). It was concluded that extract of tomato paste has an effect on the removal of extrinsic stain on the surface of teeth, acrylic resin denture teeth, and denture base. Keywords : Extrinsic stain, tomato, teeth, acrylic resin denture teeth, acrylic resin denture base.